Role of Versican, Hyaluronan and CD44 in Ovarian Cancer Metastasis - Ween, Miranda P. (Molecular Diversity Preservation International (MDPI), 2011)
There is increasing evidence to suggest that extracellular matrix (ECM) components play an active role in tumor progression and are an important determinant for the growth and progression of solid tumors. Tumor cells interfere with the normal programming of ECM biosynthesis and can extensively modify the structure and composition of the matrix. In ovarian cancer alterations in the extracellular environment are critical for tumor initiation and progression and intra-peritoneal dissemination. ECM molecules including versican and hyaluronan (HA) which interacts with the HA receptor, CD44, have been shown to play critical roles in ovarian cancer metastasis. This review focuses on versican, HA, and CD44 and their potential as therapeutic targets for ovarian cancer.